Coordination of the Process of Creation, Implementation and Adaptation of Innovative Technologies by Russian Companies - Elena А. BORKOVA; Natalia V. Sopina; Elena A. MUTAREVA; Lina V. VATLINA; Tatiana N. RODIONOVA (Communications of International Proceedings, 2020)
Innovative development is relevant for companies of any type, size and any specificity. Global trends, such as the emergence of new disruptive technologies, digitalization and accelerated product life cycles, are driving radical changes in most industries. Changing value chains, shifting profitability zones, emerging new players - and this fundamentally changes the balance of power in industries, significantly accelerating the introduction of new ideas and developments. Every year new technologies penetrate our life faster and faster, and companies have less time to implement them. As a result, the usual structure of industries is changing: the share of innovative companies in many sectors already reaches 10-20% and will grow rapidly in the coming years. Thus, a prerequisite for the leadership of companies in the market and the guarantee of sustainable competitive advantage is the need to use a wide range of innovative levers. Today, in order to gain a significant place in the industry, any company needs to comprehensively engage in innovations, applying all three of their main types - product innovations, process innovations and innovations in building a business model.
Keywords: Innovations; Innovative Development; Innovative Technologies; Global Trends; Investments; Economic Growth; Solar Energy; Ecology.